Valuing the Time of the Self-Employed - Agness, Daniel; Baseler, Travis; Chassang, Sylvain; Dupas, Pascaline; Snowberg, Erik (Review of Economic Studies, 2025)
Abstract People’s value of their own time is a key input in public policy evaluations—these evaluations should account for time taken away from work or leisure as a result of policy. Measuring this value for the self-employed is challenging, as, by definition, it is not priced by the market. Using rich choice data collected from farming households in western Kenya, we show that households exhibit non-transitive preferences. As a result, neither market wages nor standard valuation techniques correctly measure participants’ value of time. Using a structural model, we identify the behavioural wedges in participants’ choices and find that distortions appear when households exchange cash either for time or for goods. Our model estimates suggest that valuing the time of the self-employed at 60% of the market wage is a reasonable rule of thumb.